RETRACTED: Neoadjuvant Therapy for Esophageal Adenocarcinoma in the Community Setting—Practice and Outcomes - Abdo, Joe; Bertellotti, Carrie A.; Cornell, David L.; Agrawal, Devendra K.; Mittal, Sumeet K. (Frontiers in Oncology, 2017)
There has been an alarming rise in the incidence of esophageal adenocarcinoma and it continues to have poor survival in part due to lack of effective chemotherapy and presentation at advanced stages. Over a dozen chemotherapeutic agents are FDA approved for esophageal cancer (EC), and a two or three-drug combination is typically prescribed as first-line therapy for the majority of EC patients, either pre or post-operatively with esophageal resection. We have noticed significant variability in adjuvant and neoadjuvant regimens used in the community setting. The aim of this study was to review various drug regimens used in the neoadjuvant setting for esophageal cancer patients with adenocarcinoma undergoing resection at a single tertiary referral center in the Midwest. A total of 123 patients (stage II-III) underwent esophageal resection after neoadjuvant treatment at the center. Overall, 18 distinct drug regimens were used in 123 patients including two patients receiving targeted therapy. Median survival post-surgery for this group was 11.2 months with no single regimen offering a survival advantage. These results reveal an unclear algorithm of how accepted regimens are prescribed in the community setting as well as a dire need for agents that are more effective. Additionally, it was noted that although proteomic markers have been found to predict drug response to 92% of the FDA approved drugs in esophageal cancer (12 of 13), according to pathology reports, molecular diagnostics was not used to direct treatment in this cohort. We propose potential strategies to improve clinical outcomes including the use of a robust molecular diagnostic panel and the potential role for targeted chemotherapy and/or immunotherapy in the management of esophageal cancer patients.